Integrating transcriptomics and metabolomics to analyze quinoa (Chenopodium quinoa Willd.) responses to drought stress and rewatering - Huan, Xiuju; Li, Li; Liu, Yongjiang; Kong, Zhiyou; Liu, Yeju; Wang, Qianchao; Liu, Junna; Zhang, Ping; Guo, Yirui; Qin, Peng (Frontiers in Plant Science, 2022)
The crop production of quinoa (Chenopodium quinoa Willd.), the only plant meeting basic human nutritional requirements, is affected by drought stress. To better understand the drought tolerance mechanism of quinoa, we studied the leaves of a high-generation, drought-resistant quinoa strain (“Dian li-129”) during the seedling stage after drought and rewatering treatments using transcriptomics and targeted metabolomics. Drought-treatment, drought control, rewatering-treated, and rewatered control were named as DR, DC, RW, and RC, respectively. Among four comparison groups, DC vs DR，RC vs RW, RW vs DR, and RC vs DC, we identified 10292, 2307, 12368, and 3 differentially expressed genes (DEGs), and 215, 192, 132, and 19 differentially expressed metabolites (DEMs), respectively. A total of 38670 genes and 142 pathways were annotated. The results of transcriptome and metabolome association analysis showed that gene-LOC110713661 and gene-LOC110738152 may be the key genes for drought tolerance in quinoa.Some metabolites accumulated in quinoa leaves in response to drought stress, and the plants recovered after rewatering. DEGs and DEMs participate in starch and sucrose metabolism and flavonoid biosynthesis, which played vital roles in quinoa during drought. Drought tolerance of quinoa was correlated with gene expression differences, metabolite accumulation and good recovery after rewatering. These findings improve our understanding of drought and rewatering responses in quinoa and have implications for the breeding of new drought-tolerance varieties while providing a theoretical basis for their identification.